Characterization of gas-liquid flows in rectangular bubble columns using conductivity probes - Buwa, Vivek V.; Ranade, Vivek V. (Chemical Engineering Communications, 2005)
Unsteady gas-liquid flows in bubble columns are comprised of various flow processes occurring with varying length and time scales and govern mixing and transport processes. In the present work, we have characterized dynamic and time-averaged properties of gas-liquid flows in rectangular bubble columns using conductivity probes. The development of a single-tip conductivity probe, data processing methodology, and photographic validation procedure is discussed in detail. The effect of superficial gas velocity and aerated liquid height-to-width ( H/W) ratio on voidage fluctuations and time-averaged gas holdup was investigated. The experimental data presented here can help in understanding the dynamics of various flow processes and validating computational fluid dynamics based models.
Keywords: Bubble column; gas holdup; gas-liquid flows; voidage fluctuations

Comparison of flow structures in spacer-filled flat and annular channels - Ranade, Vivek V.; Kumar, Anil (Desalination, 2006)
Spacers are designed to create directional changes in the flow through membrane modules. Such secondary flow structures reduce concentration polarization and membrane fouling. Obviously, type of the spacer used in membrane modules strongly influences the resulting flow and therefore performance of the module. In this work, we have modeled detailed fluid dynamics of spacer filled channels by using the `unit cell' approach. The validated computational fluid dynamics (CFD) model was used to evaluate performance of certain spacer shapes and compare the resulting fluid dynamics in flat and curved channels. The simulations show that fluid flow behavior in a spacer-filled flat and a spiral channel was not significantly different. This means that pressure drops and mass transfer coefficients measured in flat channels may provide adequate guidelines, which would also be valid for spiral-wound modules. The results presented in this work will have significant implications for identifying improved spacers with higher propensities to reduce fouling in membrane modules.
International Congress on Membranes and Membrane Processes, Seoul, SOUTH KOREA, AUG 21-26, 2005
Keywords: annular channel; CFD; flat channel; membrane spacers

Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow

Hydrodynamics of bubble column reactors at high gas velocity: experiments and computational fluid dynamics (CFD) Simulations - Rampure, Mohan R.; Kulkarni, Amol A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2007)
This paper focuses on the modeling of flow and mixing in a bubble column reactor operated at high gas velocities (up to 0.40 m/s). A dual-tip conductivity probe was used to measure local void properties such as local time-averaged gas holdup, chord length distribution, bubble velocity distribution, and interfacial area. Chord length distribution was converted to bubble size distribution, using the backward transformation method. Liquid-phase mixing time measurements were conducted using a conductivity probe. A computational fluid dynamics (CFD) model was developed to simulate the unsteady gas-liquid flow in a bubble column using commercial code FLUENT 6.2. The time-averaged flow properties predicted by CFD simulations were compared with the experimental data. The role of unsteady flow structures in mixing was studied. The `' multiple snapshots `' approach was used to simulate the mixing time using CFD. The mixing times that were predicted for all superficial gas velocities compared favorably to the measured values. This study of the hydrodynamic behavior of a bubble column at higher gas velocity provides a basis for understanding and simulating solid suspension (or solid mixing) in slurry bubble column reactors.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
8th International Conference on Gas-Liquid and Gas-Liquid-Solid Reactor Engineering, Indian Inst Technol Delhi, New Delhi, INDIA, DEC 16-19, 2007
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation

Preface: CAMURE-6 & ISMR-5 symposium in Pune, India - Chaudhari, Raghunath V.; Ranade, Vivek V. (Industrial & Engineering Chemical Research, 2007)

Rotary Cement Kiln Simulator (RoCKS): integrated modeling of pre-heater, calciner, kiln and clinker cooler - Mujumdar, Kaustubh S.; Ganesh, K. V.; Kulkarni, Sarita B.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
This paper presents an integrated reaction engineering based mathematical model for clinker formation in cement industry. Separate models for pre-heater, calciner, rotary kiln and cooler were initially developed and coupled together to build an integrated simulator. Appropriate models for simulating gas-solid contact and heat transfer in pre-heaters were developed. Calciner was modeled by considering simultaneous combustion of coal particles and calcination of raw meal. Complex heat transfer and reactions (solid-solid, gas-solid and homogeneous reactions in gas phase) in rotary kiln were modeled using three sub-models coupled to each other. Solid-solid reactions in the bed region of the kiln were modeled using pseudo-homogeneous approximation. Melting of solids in the bed and formation of coating within the kiln were accounted. Clinker cooler was simulated by developing a two-dimensional model to capture cross-flow heat transfer between air and hot clinkers. The individual models were coupled with each other via mass and energy communication through common boundaries. The coupled model equations were solved iteratively. The model predictions agree well with the observations and experience from cement industry. The model was used to gain better understanding of influence of operating conditions on energy consumption in cement plant. Several ways for reducing energy consumption were computationally investigated. The integrated model, the developed software RoCKS (for Rotary Cement Kiln Simulator) and results presented here will be useful for enhancing our understanding and for enhancing the performance of clinker manufacturing. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: cement; energy consumption; reaction engineering model

Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet

CFD modeling of rotary cement kilns - Mujumdar, Kaustubh S.; Ranade, Vivek V. (Asia-Pacific Journal of Chemical Engineering, 2008)
Rotary cement kilns are widely used to convert calcineous raw meal into cement clinker, and are key components in the cement industry. In this article, we report a comprehensive computational fluid dynamics (CFD)-based model to capture key transport processes in rotary cement kilns. Separate but coupled computational models were developed for the bed and the freeboard regions of the rotary kiln. The complex swirling airflow produced by kiln burners, coal combustion, gas-phase combustion of volatile matter and radiative heat transfer in the freeboard region were modeled. The clinkerization reactions in the bed region were modeled assuming solids as pseudo fluids. Coating formation in cement kilns (for both bed and freeboard regions) was considered. Appropriate source and sink terms were developed to model transfer of CO(2) from the bed to the freeboard region due to calcination reaction in the bed region. The developed bed and freeboard models were coupled by mass and energy communication through common interface. These coupled computational models were able to quite satisfactorily predict the available data from industrial kilns and previously published results. The computational models were also able to capture the intricacies of the burning zones of rotary cement kilns for changing burner-operational parameters like axial to swirl ratio and oxygen enrichment. The developed approach, computational models and simulation results will not only help in developing better understanding of cement kilns but also provide quantitative information about influence of burner design and other design parameters on kiln performance. (C) 2008 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: burner; CFD; coal combustion; rotary cement kiln

Guest editorial: computational fluid dynamics - Ranade, Vivek V.; Pareek, Vishnu (Asia-Pacific Journal of Chemical Engineering, 2008)

Modeling of a fluidized bed propylene polymerization reactor operated in condensed mode - Utikar, Ranjeet P.; Harshe, Yogesh M.; Mehra, Anurag; Ranade, Vivek V. (Journal of Applied Polymer Science, 2008)
The gas-phase polymerization of propylene is one of the most widely accepted and commercially used processes for the manufacture of polypropylene (PP). Because of the highly exothermic nature of polymerization reactions, temperature runaway and subsequent polymer melting and agglomeration may occur, and the reactor has to be operated in a small operating window for safety. The addition of liquid monomer for heat removal (condensed mode) broadens the operating window and can substantially increase (by 50-100%) the capacity of given reactor hardware. This article describes the extension of a comprehensive mathematical model for the simulation of fluidized bed PP reactors to include the condensed mode of operations. The model is used to determine the influence of the operating parameters on the polymer properties and particle size distribution. The model is also used to determine the effects of two active sites and the reaction kinetics on macroscopic variables. The developed framework is useful for simulating multimonomer, multisite Ziegler-Natta-type olefin fluidized bed polymerization reactors operated under condensed mode. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 108: 2067-2076, 2008.
Keywords: Modeling; Polyolefins; Ziegler-Natta polymerization

Pressure drop across vortex diodes: experiments and design guidelines - Kulkarni, Amol A.; Ranade, Vivek V.; Rajeev, R.; Koganti, S. B. (Chemical Engineering Science, 2009)
Vortex diodes are used as leaky non-return valves in applications where it is desirable to avoid valves with moving parts. Despite their use in practice for several decades, no clear guidelines for design and optimization of vortex diodes are available. Detailed experimental study on flow and pressure drop characteristics of vortex diodes was therefore carried out to evolve such guidelines. The study covered a wide range of vortex diodes. The variation of diodicity (ratio of pressure drop for reverse and forward flow for the same flow rate) with respect to diode geometry, diode size (d(c)), aspect ratio (d(c)/h), nozzle configuration and Reynolds number (Re) was studied. The experimental results were critically analyzed to develop a design methodology. The methodology is shown to be useful for obtaining the diode dimensions that would yield the desired diodicity for the required operating flow rate. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aspect ratio; Diodicity; Nozzles; pressure drop; Vortex diode

Solid suspension and liquid phase mixing in solid-liquid stirred tanks - Sardeshpande, Madhavi V.; Sagi, Aparna R.; Juvekar, Vinay A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2009)
Stirred tanks are widely used in chemical process industries for catalytic reactions, dissolution of solids, crystallization, and so oil. In designing and optimizing such processes, suspension quality Of Slurry is an important parameter. Suspension quality depends upon complex interactions of impeller generated flow, turbulence, and solid loading. Most of the earlier work on solid suspension focuses Oil identifying critical impeller speed for just suspension of solids (N(js)). In this study, apart from N(js) aspects like cloud height and liquid phase mixing in solid-liquid suspensions were also studied A new way of characterizing solid-liquid suspensions and liquid phase mixing using nonintrusive wall pressure fluctuation measurements has been developed. Systematic experimental data on N(js), cloud height, power consumption, mixing time, and circulation time over a range of solid volume fraction and impeller speeds have been presented here. The results and discussion presented here will have useful implications for designing solid-liquid stirred tanks.

Hysteresis in cloud heights during solid suspension in stirred tank reactor: experiments and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Aiche Journal, 2010)
Solid suspension in stirred tank reactor is widely used in process industries for catalytic reactions, dissolution of solids, crystallization, and so on. Suspension quality is a key issue in design and operation of stirred reactor and its determination is not straight forward. Cloud height measurements of solid suspension provide a relatively simple way to quantify quality of suspension. In this work, experiments were carried out to quantify variation of cloud heights with impeller speed and particle characteristics. These measurements were carried out using visual observations, image analysis, and ultrasound velocity profiler techniques. The obtained data demonstrated the existence of hysteresis in cloud heights with respect to impeller speed. Apart from possible applications in reducing power required for achieving desired solid suspension quality, the existence of hysteresis also provides a new way to evaluate computational fluid dynamics (CFD) simulations of solid liquid flows in stirred vessels. An attempt was made to capture observed hysteresis in cloud heights in CFD simulations. The simulated results were compared with the experimental data. The presented models and results (experimental and computational) will he useful for simulating complex solid liquid flows in stirred reactors. (C) 2010 American Institute of Chemical Engineers AIChE J, 56: 2795-2804, 2010
Keywords: CFD; hysteresis in cloud height; solid velocity profiles

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Computational fluid dynamics modelling of solid suspension in stirred tanks - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Current Science, 2012)
Solid suspension and mixing are crucial in many important processes, including multiphase catalytic reactions, crystallization, precipitation, etc. In recent years, various efforts have been made to numerically simulate solid-liquid flows in stirred vessels using computational fluid dynamics (CFD). In this article, we present a brief account of our group's efforts at developing and using CFD models for simulating solid suspension in stirred tanks. Computational models were developed and evaluated by comparing model predictions with our data as well as published experimental data. A variety of experimental techniques ranging from torque and wall pressure fluctuations to ultrasound velocity profiler were used. Efforts were made to develop appropriate sub-models for capturing influence of the prevailing turbulence and solid volume fraction on effective inter-phase coupling terms. A hysteresis in variation of the height of the cloud of suspended solid with impeller rotational speed was observed. The hysteresis, besides having applications in realizing better suspension at lower effective power consumption, also offers an attractive evaluation test for CFD models. A new way to carry out dynamic settling of solid cloud by sudden impeller stoppage has been developed. The approach, models and results presented here will be useful for extending applications of CFD models for simulating industrial stirred slurry reactors as well as further research in the field.
Keywords: computational fluid dynamics; hysteresis; solid suspension; stirred tanks

Isophorone reactor: modelling and performance enhancement - Darda, Pranay J.; Ranade, Vivek V. (Chemical Engineering Journal, 2012)
The production of isophorone in a reactive distillation column was modelled. Mass transfer and heat transfer accompanied by chemical reactions were incorporated in a dynamic non-equilibrium multistage model. A base case simulation was identified and established. The base case simulation showed the value of key performance indicator that is mass ratio of acetone consumed to isophorone produced as 1.54. The computational model was then used to understand and to evaluate influence of various key design and operating parameters on this key performance indicator. Influence of reactor volume, mass transfer coefficient and feed composition, location and temperature was evaluated. The simulated results indicate that the key performance indicator can be improved (reduce acetone consumed per isophorone produced) by manipulating acetone content in the feed and location of the feed. The presented results will be useful for realising performance enhancement of isophorone and other similar reactors. (C) 2012 Elsevier B.V. All rights reserved.
22nd International Symposium on Chemical Reaction Engineering (ISCRE), Maastricht, NETHERLANDS, SEP 02-05, 2012
Keywords: Isophorone; Model; Performance enhancement; Reactive distillation

Modeling of liquid propellant combustion chamber - Pandit, Ajinkya V.; Kumar, Ashok; Rao, G. Srinivasa; Kedarnath, C.; Srihari, R.; Ranade, Vivek V. (Chemical Engineering Journal, 2012)
Liquid propellants are fuels which do not require external supply of oxygen for combustion. These fuels are widely used for propulsion applications in oxygen rare environments (underwater, space). We had previously presented a model for solid propellant decomposition in a combustion chamber. In this study we extend the model for the case of combined solid and liquid propellant combustion. Sub-models relating to solid propellant combustion and outlet flow-rate in the present study are borrowed from the previous study. The combustion chamber is assumed to be a `well-mixed reactor'. A model is developed to characterize the liquid propellant spray assuming the spray is a collection of individually burning droplets. A single droplet decomposition model was developed and used along-with the spray model to solve for the liquid propellant burning rate. Appropriate numerical methods and computer programs were developed to solve the model equations. The model predictions were compared with the experimental data obtained in earlier studies. Appropriate methodology for calibrating the model parameters was developed and its usefulness was demonstrated by comparing the simulated pressure profiles with the experimental pressure profiles. The presented model and results will be useful for selecting appropriate liquid propellants for propulsion systems and for the development of a system level model of propulsion systems. (C) 2012 Elsevier B.V. All rights reserved.
22nd International Symposium on Chemical Reaction Engineering (ISCRE), Maastricht, NETHERLANDS, SEP 02-05, 2012
Keywords: Liquid propellant; Single droplet decomposition; Spray combustion

Simulation of settling of solid particles due to sudden impeller stoppage - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2012)
Stirred tank reactors (STRs), which are used in process industries (for a variety of operations, such as catalytic reactions, dissolution of a solid, crystallization, and so on), often involve handling of solid liquid (gas) systems. The solid suspension and the quality of the suspension are key issues in the design and operation of such stirred reactors. Despite extensive experimental work over previous decades, comprehensive understanding and reliable methods to predict the solids suspension and the quality of the suspension are not yet available. Advances in computational fluid dynamics (CFD) and new experimental techniques offer potentially effective ways of understanding solids suspension in stirred tanks. The present work highlights the potential of using transient measurements by way of the dynamic settling of solid particles because of the sudden stoppage of an impeller to evaluate CFD models. Sudden impeller stoppage results in significantly different conditions, in terms of the ratio of particle diameter to Kolomogorov length scale (d(p)/lambda), as well as the solids volume fraction experienced by solid particles. Therefore, experimental data under such sudden impeller stoppage offer a better way to evaluate the influence of prevailing turbulence and solids volume fraction on effective drag and therefore offer a more-stringent test to CFD models than steady-state profiles. Besides facilitating the development of computational models, the experimental and simulation studies of sudden impeller stoppage also provide useful data to gain insight into the behavior of the stirred tank after abrupt impeller stoppage due to sudden power failure.

Crystallization: key thermodynamic, kinetic and hydrodynamic aspects - Vedantam, Sreepriya; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Crystallization is extensively used in different industrial applications, including the production of a wide range of materials such as fertilizers, detergents, food and pharmaceutical products, as well as in the mineral processing industries and treatment of waste effluents. In spite of the wide-spread use of crystallization, a clear understanding of the thermodynamic, kinetic and hydrodynamic aspects of the design methodologies are not yet well established. More often than not crystallization is still considered an art especially in fine-chemicals, pharmaceuticals and life-sciences sector. It is essential to understand and relate key thermodynamic, kinetic and hydrodynamic aspects to crystallizer performance, not just in terms of yield but also in terms of product quality (characterized by particle size distribution, morphology, polymorphism and the amount of strain as well as the uptake of solvent or impurities in the crystal lattice). This paper attempts to do that by critically reviewing published experimental and modelling studies on establishing and enhancing state-of-the-art thermodynamic, kinetic and hydrodynamic aspects of crystallization. Efforts are made to discuss and raise points for emerging modelling tools needed for a flexible design and operation of crystallizers and crystallization processes that are needed to meet the ever increasing demand on precise product specifications. Focus is on bringing out the trends which can be used as perspectives for future studies in this field.
Keywords: CFD; Crystallization; growth; Nucleation; polymorphism; supersaturation

Direct contact heat transfer via injecting volatile liquid in a hot liquid pool: generation and motion of bubbles - Kulkarni, Amol A.; Ranade, Vivek V. (Chemical Engineering Science, 2013)
Direct contact heat transfer via injection of volatile liquid is an effective strategy for removing heat from a viscous liquid pool. The rapid evaporation effectively removes heat and the generated bubbles move quickly to the top surface. In this paper, we present an experimental and phenomenological analysis of the evaporation of a drop in a slightly miscible liquid. The phenomenon was visualized using a two-dimensional transparent experimental set-up with a single inlet at the bottom. The videos were used to estimate bubble dimensions, its rise velocity, distance from the detachment point, and fraction of vapor and the liquid phases in the evaporating drop. The initial drop size, temperature difference between the hot fluid and the low boiling solvent and the nucleation rate governed the rate of change of the drobble (combined entity of drop and bubble) diameter and its rise velocity. A phenomenological model describing transient behavior of drobble (motion and heat transfer) is developed. The transient variation in the interfacial areas for heat transfer and the projected area were found to have effect on the predictions. The model and results will also provide useful basis for extending the work towards better understanding of direct contact heat transfer in viscous systems like polymerization reactors. (C) 2013 Elsevier Ltd. All rights reserved.
11th International Conference on Gas-Liquid and Gas-Liquid-Solid Reactor Engineering (GLS) Held in Conjunction with 9th World Congress on Chemical Engineering (WCCE) / Asian Pacific Conference on Chemical Engineering (APCChE), Seoul, SOUTH KOREA, AUG 19-22, 2013
Keywords: Bubble; Direct contact HT; Drobble; Drop; Evaporation; Slightly miscible liquids

Flow and heat transfer in serpentine channels - Karale, Chaitanya M.; Bhagwat, Sunil S.; Ranade, Vivek V. (Aiche Journal, 2013)
Serpentine channels are often used in microchannel reactors and heat exchangers. These channels offer better mixing, higher heat and mass-transfer coefficients than straight channels. In the present work, flow and heat transfer experiments were carried out with a serpentine channel plate comprising of 10 units (single unit dimensions: 1 x 1.5 mm(2) in cross section, length 46.28 mm, D-h 1.2 mm) in series. Pressure drop and heat-transfer coefficients were experimentally measured. Flow and heat transfer in the experimental set-up were simulated using computational fluid dynamics (CFD) models to understand the mechanisms responsible for performance enhancement. The CFD methodology, thus, developed was applied to understand the effect of various geometrical parameters on heat transfer enhancement. A criterion was defined for evaluation of heat transfer performance (heat transfer per unit pumping power), thus, ensuring due considerations to required pumping power. The effect of geometrical parameters and the corresponding mechanisms contributing for enhancement are discussed briefly. Based on the results, a design map comprising different serpentine channels showing heat transfer enhancement with pumping power was developed for Reynolds number of 200 which will be useful for further work on flow and heat transfer in serpentine channels. (C) 2012 American Institute of Chemical Engineers AIChE J, 59: 1814-1827, 2013
Keywords: computational fluid dynamics; heat transfer; pressure drop; serpentine

Multiphase flows with phase change foreword - Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)

Two-phase flow boiling in small channels: a brief review - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Boiling flows are encountered in a wide range of industrial applications such as boilers, core and steam generators in nuclear reactors, petroleum transportation, electronic cooling and various types of chemical reactors. Many of these applications involve boiling flows in conventional channels (channel size >= 3 mm). The key design issues in two phase flow boiling are variation in flow regimes, occurrence of dry out condition, flow instabilities, and understanding of heat transfer coefficient and vapor quality. This paper briefly reviews published experimental and modeling work in these areas. An attempt is made to provide a perspective and to present available information on boiling in small channels in terms of channel size, flow regimes, heat transfer correlations, pressure drop, critical heat flux and film thickness. An attempt is also made to identify strengths and weaknesses of published approaches and computational models of boiling in small channels. The presented discussion and results will provide an update on the state-of-the-art and will be useful to identify and plan further research in this important area.
Keywords: Boiling; dry-out; heat transfer; instabilities; small channel; two-phase flow

Crystal shape evolution using polyhedral population balance - Shaikh, Latif J.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2014)
Research on crystal morphology covers shape evolution of single crystal and evolution of the size and shape distribution of populations of crystals. The population balance models have been used for the single or multiple dimensions for predicting the evolution of crystal size distributions (CSDs). More often than not these models do not consider the change in solute concentration due to disappearance/appearance of the crystal faces and therefore compromise rigorous mass balance. The present work focuses on the methodology for the morphological evolution of crystal shape using a polyhedral population balance model. This methodology is based on the morphodrome which illustrates the shapes of crystals at various operating conditions. gPROMS software (PSE, UK) along with Microsoft Excel is used to devise the framework for predicting the crystal shape evolution. The developed approach and models can be implemented for various crystallization systems and will be useful for simulating crystal shape evolutions.

Engineering reactors for catalytic reactions - Ranade, Vivek V. (Journal of Chemical Sciences, 2014)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst which provides an alternative route of reaction with lower activation energy and better control on selectivity can make substantial impact on process viability and economics. Extensive studies have been conducted to establish sound basis for design and engineering of reactors for practising such catalytic reactions and for realizing improvements in reactor performance. In this article, application of recent (and not so recent) developments in engineering reactors for catalytic reactions is discussed. Some examples where performance enhancement was realized by catalyst design, appropriate choice of reactor, better injection and dispersion strategies and recent advances in process intensification/ multifunctional reactors are discussed to illustrate the approach.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: Catalyst; effectiveness; engineering; hydrodynamics; reactors

CRE for magic(modular, agile, intensified & continuous) processes - Ranade, Vivek V.; Sharma, Mrityunjay K.; Kulkarni, Amol A. (Chemical Engineering Journal, 2015)
Fine and specialty chemical industry caters to several key applications required for maintaining and enhancing quality of life. Most of these fine and specialty chemicals are still manufactured in stirred tank reactors operated in batch or semi-batch modes. A paradigm shift is necessary to transform these into new age, efficient and continuous processes and plants. In this paper, recent attempts of our group on developing MAGIC (modular, agile, intensified and continuous) devices, processes and plants for fine and specialty chemicals industry are discussed. The focus is on key chemical reaction engineering aspects of developing MAGIC processes. An attempt is made to evolve guidelines for designing MAGIC devices and reactors. The discussion will be useful to researchers as well as to industry practitioners. (C) 2014 Elsevier B.V. All rights reserved.
23rd International Symposium on Chemical Reaction Engineering (ISCRE), Bangkok, THAILAND, SEP 07-10, 2014
Keywords: Agile; Continuous; CRE; Intensified; Modular

Development of newer adsorbents: activated carbons derived from carbonized cassia fistula - Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Salvi, Monal S.; Jain, Saijal; Hadawale, Snehal D.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia fistula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms of the derived adsorbents produced by thermal and chemical activation was examined for two representative cases, desulfurization of transportation fuels and wastewater treatment. The adsorbents were characterized by FTIR, XRD, XPS, and SEM techniques that indicate specific characteristics useful as an adsorbent. A successful application in the real industrial wastewater treatment and comparison with well recognized commercial adsorbents clearly highlights the utility of the developed newer adsorbents in separation science and technology.

Flow in vortex diodes - Pandare, Aditya; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
A vortex diode is used as a cavitation device for treatment of industrial waste water and also, as a leaky non-return valve in nuclear applications. It consists of a vortex chamber with an axial and tangential port. When the fluid is injected through the tangential port, a strong vortex flow is set up in the diode chamber. This flow is characterized by phenomena such as vortex transition, precessing vortex core, toroidal recirculation zone, reverse flow core and recirculation zone in the axial port. Although studies have been conducted on the ``confined vortex'' class of flows (and some of them on vortex diodes), none of them provides a collective account of key nuances of the flow in a vortex diode. The flow in the diode differs from other confined-vortex flows on account of the axial-velocity deficit, due to which, direct correlations from other confined vortex flows cannot be applied to the diode. This work attempts to address the aforementioned flow characteristics in the diode using results primarily from CFD simulations. The reported methodology, computational model and results will be useful to gain better understanding of flows in vortex diodes and to optimize designs of vortex diodes for variety of applications. (C) 2015 Published by Elsevier B.V. on behalf of The Institution of Chemical Engineers.
Keywords: CFD; Confined vortex; Diode; Precessing vortex core; Recirculation

Generic framework for crystallization processes using the population balance model and its applicability - Shaikh, Latif J.; Bari, Atul H.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2015)
A generic modeling framework for batch cooling crystallization processes has been developed to understand the crystallization process from operational and modeling point of view. The generic framework for crystallization process modeling incorporates the characteristic dimensions of crystals and polymorphic transformation, as well as the hydrodynamic mixing effects in the crystallizer. This Polyhedral Polymorphic Multizonal Population Balance (PPMPBM) model considers bottom-up and top-down approaches for specific systems with specific targets. The PPMPBM framework allows switching between complex and simple models to study different crystallization systems with different scenarios and combination thereof. This framework uses gPROMS software (PSE, UK) and the Microsoft Excel front-end, along with the Polytope module in Matlab, to predict the crystal size and shape evolution as well as supersaturation profiles inside the crystallizer, which can be implemented for various crystallization systems.

Heat transfer and mixing in flow through pinched pipe - Hasabnis, Nilesh S.; Totlani, Kartik A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2015)
There is an increasing trend of using tubular reactors either with passive or active augmentation methods for process intensification. A new passive method with pinching of pipe' is proposed and investigated for its performance. In the present work, initially, flow in a pinched pipe was studied experimentally and the same was reproduced numerically. The computational model was then used to investigate influences of key geometrical parameters of pinched pipe configuration on pressure drop, heat transfer, and mixing. The simulated results obtained with the pinched pipe were compared with a straight pipe, and with a commonly-used passive augmentation method (twisted tape inserts). The pinched pipe configuration offers better performance and more flexibility in manipulating heat transfer and mixing in intensified devices.
Keywords: computational fluid dynamics (CFD); heat transfer; mixing; pinched pipe; pressure drop

Modeling hysteresis during crystallization and dissolution: application to a paracetamol-ethanol system - Pandit, Ajinkya V.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Crystallization and dissolution processes are of great scientific and commercial interest. Significant efforts have been made in the past to develop mathematical models to describe these processes. In this work, observed hysteresis in particle counts during the crystallization and dissolution processes was used to develop and to test the mathematical models of crystallization and dissolution. Crystallization and dissolution experiments were performed with a system of paracetamol and ethanol. An undersaturated solution was first cooled at a particular rate causing crystallization and crystal growth. The solution was then reheated at the same rate to completely dissolve the generated particles. The particle counts and particle size distribution were measured online using a focus beam reflectance measurement (FBRM) probe. A hysteresis was observed in particle counts with respect to the solution temperature. It was also observed that this hysteresis was affected by the applied heating/cooling rates (0.3, 0.5, and 0.7 K/min) for of the solution. A systematic modeling framework based on the population balance equation (PBE) is developed for quantitatively capturing this hysteresis and the influence of cooling/heating rate on the hysteresis curve. A two-level approach was developed to simulate hysteresis: (a) PBE was solved using computationally efficient method of moments for the crystallization stage. This step was used to efficiently estimate values of parameters appearing in the model equations. (b) PBEs describing crystallization and dissolution were then solved using high resolution finite volume (HRFV) scheme coupled with the moving pivot method. The simulated hysteresis curve showed good agreement with the experimental data. Though simulated results over predicted the average particle (by,similar to 131%), the models were successful in qualitatively explaining the counterintuitive trends observed as the average particle size was tracked with time. The framework was thus shown to be a reliable and robust framework to model crystallization and dissolution processes. The developed approach, models, and results will be useful for simulating industrially relevant crystallization dissolution processes.

Two phase flow boiling pressure drop in small channels - Sardeshpande, Madhavi V.; Shastri, Parikshit; Ranade, Vivek V. (IUTAM Symposium on multiphase flows with phase change: challenges and opportunities, 2015)
Two-phase pressure drop, flow instability and boiling regime identifications are an essential step in the design of a variety of plant in the power and process industries. Despite the wide spread applications, significant experimental data on flow boiling in small channel is not available. In the present work, experimental set-up was designed for studying boiling flows in 19 mm ID tube and identifies flow regimes at various mass and heat flux conditions by varying inlet fluid temperature. The steady-state pressure data was collected and flow regimes identified using pressure drop and pressure fluctuations inside the channel. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: flow boiling; flow instability; pressure drop; regime identification

Void fraction measurement using electrical capacitance tomography and high speed photography - Sardeshpande, Madhavi V.; Harinarayan, Sagar; Ranade, Vivek V. (Chemical Engineering Research & Design, 2015)
Gas-liquid flows are encountered in variety of industrial applications including boilers, distillation towers, chemical reactors, oil pipelines, nuclear reactors etc. The measurement of two-phase flow parameters such as flow regime and void fraction is considerably important and play an important role in characterization of the hydrodynamic behavior of such gas-liquid two phase systems. The void fraction is a dimensionless quantity and is often termed as ``holdup or fraction'' in two-phase flows. According to industrial applications; it is essential to develop measurement technique for void fraction measurement which can work in hot and opaque systems. Therefore, an attempt was made here to establish electrical capacitance tomography (ECT) facility for measuring void fraction and flow regimes as well as develop suitable data processing methodologies. In the present work, focus was to measure void fraction using ECT technique and compares it with conventional and high speed photography technique. Therefore, that will give guidelines of using ECT technique for hot and opaque systems like boiling flows. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier BM. All rights reserved.
Keywords: ECT; Flow regimes; Two phase flow; Void fraction

Chord length distribution to particle size distribution - Pandit, Ajinkya V.; Ranade, Vivek V. (AICHE Journal, 2016)
A simple model is presented to extract the particle size distribution (PSD) from the chord length distribution measured using a focused beam reflectance measurement probe. The model can be implemented using simple spread sheeting tools and does not require the description of additional parameters as opposed to previous models. The model was validated for two systems consisting of spherical ceramic beads by comparing model predicted PSD against the PSD obtained through image analysis (IA). Then, the model was evaluated by considering various systems consisting of irregularly shaped particles (sand/zinc dust/plasma alumina). Model predictions accurately predicted the mean but over-predicted the variance of the PSD in comparison with the PSD obtained from IA. However, overall, a reasonable agreement was observed. Finally, the model was shown to be accurate in predicting PSD in comparison with the measured PSD for systems of practical relevance such as for paracetamol and p-aminophenol crystals. (c) 2016 American Institute of Chemical Engineers AIChE J, 62: 4215-4228, 2016

Differentiating process performance of various coagulants in removal of congo red and orange G dyes - Prajapati, Kavita; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Killedar, D. J.; Ranade, Vivek V. (International Journal of Chemical Reactor Engineering, 2016)
Two refractory azo dyes-Congo red and Orange G, especially at high concentrations were subjected to coagulation with different conventional coagulants and newer formulations developed from Aluminum sulfate, Iron (III) chloride, Aluminium chloride, Poly diallydimethylammonium chloride (Poly DADMAC) and Poly Aluminium Chloride (PAC). The highest COD reduction of 99 % was obtained with PAC SAB 18 (Powder Grade PAC) for Congo red at pH 4.5 while the color removal of 99 % was achieved with almost all the coagulants in the present study at specific pH within 3-8. The optimum dose for the iron-based coagulant is 200 mg/L while that of aluminum-based coagulants and PAC is 150-200 mg/L. Results showed that Orange G was more difficult to remove with a maximum COD removal of 65 % and 35 % color removal using various formulations. The combinational formulations of inorganic-inorganic and inorganic- organic produced a substantial enhancement in COD and color removal and reduced sludge. PAC-Fe30/70 produces the minimum sludge of 50 mL/g on Congo red. pH in the range 3-9 showed high reductions in COD and color (90-99 %) for Congo red while jerky rise in COD and color reduction was observed in the case of Orange G after pH 9. An attempt to understand the dye coagulation mechanism has been made based on the specific difference in dye structure and cation speciation.
Keywords: coagulation; Congo red; dye removal; Orange G; Wastewater treatment

Green approach to dye wastewater treatment using biocoagulants - Chethana, M.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Raja, S.; Ranade, Vivek V. (ACS Sustainable Chemistry & Engineering, 2016)
The present study focuses on newer biocoagulants, bioformulations, and the understanding of coagulant behavior with biocoagulants in relation to chemical coagulants. Newer biocoagulants, seeds of Azadirachta indica (AI) and pads of Acanthocereus tetragonus, are discussed along with two known biocoagulants, Moringa oleifera and Cicer arietinum seeds. Dye removal studies were carried out using widely reported Congo red dye to facilitate easy comparison with other conventional coagulants and the effect of various parameters such as initial dye concentration, pH, coagulant dose, etc. are discussed in detail. The use of biocoagulant was found to be highly effective, and up to 99% dye removal was achieved for coagulant doses in the range of 300-1500 mg/L. It was also observed that coagulation is pH sensitive, similar to chemical coagulants. Although the biocoagulant dose is relatively higher than the conventional chemical coagulants, a good value for the sludge volume index, similar to 50 mL/g for 1 h and 30 min, respectively, was obtained for the two coagulants, Acanthocereus tetragonus and Moringa oleifera. A very high particle count compared to chemical coagulants was observed using a focused beam reflectance measurement. Bioformulation with chemical coagulants such as alum, ferric, and aluminum based coagulants can, not only lower doses of biocoagulants (up to one-third) but can also result in significant improvement in the coagulation performance, up to 50% or more.
Keywords: coagulation; dye removal; Effluent treatment; flocculation; pollution

Industrial wastewater treatment for fertilizer industry a case study - Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Desalination and Water Treatment, 2016)
Wastewaters from chemical fertilizer industry mainly contain organics, alcohols, ammonia, nitrates, phosphorous, heavy metals such as cadmium and suspended solids. The nature of effluent streams varies in terms of its constituents and complexity. The present work attempts to fill the void in the literature that mostly reports synthetic wastewater treatment studies, by evaluating effluent treatment solutions and comparison of different methods for real wastewaters from the fertilizer industry. An attempt has been made to devise suitable methodology mainly using a new device in the form of vortex diode for hydrodynamic cavitation and also using adsorption, for several real wastewater streams from different locations in one major fertilizer industry of Maharashtra, India. The strategy involved characterization of wastewaters, studies on the effective removal of chemical oxygen demand (COD) and devising solutions for effective reduction in ammoniacal nitrogena more serious issue in the fertilizer industry. The characterization of wastewaters from different streams revealed huge variation in COD from 50 to 140,000ppm and ammoniacal nitrogen from 6 to 1,700ppm. Some effluent streams contained alcohol up to 5%. Hydrodynamic cavitation using vortex diode and adsorption with modified carbons were used to treat these streams. Cavitation studies were carried out on a pilot plant and the effect of pressure drop, cavitating device and process intensification were studied. It was observed that the effluent treatment strategy requires careful identification and application of suitable treatment method on the basis of the nature of the effluent. Also, hydrodynamic cavitation, using vortex diode appears to be techno-economically attractive option in treating fertilizer wastewaters giving a very high reduction in COD and ammoniacal nitrogen (up to 85%), similar to adsorption. The results clearly identify potential of newer methodologies in the treatment of effluents in the fertilizer industry.

Mixing studies in unbaffled stirred tank reactor using electrical resistance tomography - Sardeshpande, Madhavi V.; Kumar, Gaurav; Aditya, T.; Ranade, Vivek V. (Flow Measurement and Instrumentation, 2016)
Unbaffled stirred tanks are extensively used in chemical process industries for variety of applications including semi-batch reactions. In un-baffled stirred tanks, impeller rotation generates a vortex and reactants are added into this vortex. There is a growing interest towards understanding the mixing performance of such unbaffled stirred vessels. The present work is aimed at providing experimental results on mixing time and solid particle distribution inside an unbaffled vessel using electrical resistance tomography (ERT). A methodology for using ERT for characterizing vortex and mixing in unbaffled stirred vessel was established. The ERT was used to measure the mixing time with and without solid particles (glass beads, 250 mu m) in a stirred reactor. In this study, ERT technique was effectively applied for imaging solid-liquid flow and developed suitable data processing methodologies. It observed that estimated liquid phase mixing time for Un-baffled vessel was more as compared to baffled vessel. Radial solid concentration profiles showed Gaussian distribution inside the vessel. The presented methodology of using ERT and experimental results will be useful for designing and estimating mixing and solid distribution in unbaffled stirred tanks. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ERT; Mixing time; Radial solid concentration; Unbaffled stirred tank

Non-catalytic deep desulphurization process using hydrodynamic cavitation - Suryawanshi, Nalinee B.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ranade, Vivek V. (Scientific Reports, 2016)
A novel approach is developed for desulphurization of fuels or organics without use of catalyst. In this process, organic and aqueous phases are mixed in a predefined manner under ambient conditions and passed through a cavitating device. Vapor cavities formed in the cavitating device are then collapsed which generate (in-situ) oxidizing species which react with the sulphur moiety resulting in the removal of sulphur from the organic phase. In this work, vortex diode was used as a cavitating device. Three organic solvents (n-octane, toluene and n-octanol) containing known amount of a model sulphur compound (thiophene) up to initial concentrations of 500 ppm were used to verify the proposed method. A very high removal of sulphur content to the extent of 100% was demonstrated. The nature of organic phase and the ratio of aqueous to organic phase were found to be the most important process parameters. The results were also verified and substantiated using commercial diesel as a solvent. The developed process has great potential for deep of various organics, in general, and for transportation fuels, in particular.

Processing of TGA data: analysis of isoconversional and model fitting methods - Jain, Ankit A.; Mehra, Anurag; Ranade, Vivek V. (Fuel, 2016)
Thermogravimetric analysis (TGA) is routinely used to characterize coal. Apart from proximate analysis, TGA data is also used to characterize kinetics of devolatilization and char combustion. Various methods have been proposed to process the TGA data [isoconversional or model free methods such as Friedman method, Kissinger method, Flynn-Wall-Ozawa method (FWO), Kissinger-Akahira-Sunose method (KAS) or single or multi-reaction models (SRMs/MRMs) and distributed activation energy models (DAEMs)]. In this work, we have critically examined various models for processing TGA data obtained with typical Indian coal. A generalized equation has been proposed to encompass different models as special cases. We have also considered a model based on a possibility of distribution of frequency factor along with constant or distribution of activation energies. The results of TGA data described by different models were critically analyzed. The presented results and methodology will be useful for selecting appropriate strategy for processing TGA data. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: DAEM; High ash coal; Isoconversional methods; Pyrolysis; TGA

Selectivity engineering of the diazotization reaction in a continuous flow reactor - Shukla, C. A.; Kulkarni, Amol A.; Ranade, Vivek V. (Reaction Chemistry & Engineering, 2016)
In situ generated diazonium salts are useful intermediates for the synthesis of fine chemicals and active pharmaceutical ingredients. This paper presents a methodology for selectivity engineering of the diazotization reaction in a continuous reactor. The yield of diazotization was found to depend on mixing, dispersion, reaction kinetics, operating temperature and residence time. Initially, experimental data and an isothermal axial dispersion model were used for estimating mixing time. A correlation for estimating mixing time for different flow reactors is proposed. The model predictions were compared with the experimental data. The validated axial dispersion model and Central Composite Design (CCD) were used to optimize diazotization in a straight tube reactor (1.78 mL). The model was then used for scaling-up of aniline diazotization from a straight tube reactor to a proprietary AmAR3 reactor (scale-up ratio of ∼20). The initial concentration, inlet temperature, average heat capacity of the reaction mixture, mixing, residence time (distribution) and available heat transfer area per unit volume of the reactor were found to be the key parameters for scaling-up of the diazotization reaction. The presented approach and results will be useful to practicing chemists and engineers for enhancing the selectivity of diazotization reactions in continuous reactors.

Two-phase flow boiling in 19mm tube: experiments and CFD modelling - Sardeshpande, Madhavi V.; Raymond, Barlev; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2016)
Boiling flows are encountered in a wide range of industrial applications such as boilers, nuclear reactors, electronic cooling, and various types of chemical reactors. Heat transfer coefficients, flow boiling regimes, flow instabilities, pressure drops, and conditions like dry-out are some of the key issues in every boiling flow study. It is observed that a limited experimental database is available for the 19mm ID channel diameter, i.e. a typical tube diameter of steam generator. Therefore, in the present work, the experimental setup was designed for studying boiling flows in a 19mm ID tube in such a way that different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) could be investigated by varying inlet conditions. The reported results cover a reasonable range: 8-27kW/m(2) and 2.9-5.9kg/m(2)s heat and mass flux conditions, respectively. A basic computational flow model was also developed to facilitate interpretation of the obtained data. The presented design of the experimental setup and the approach of mimicking different types of steam generator tubes as well as presented experimental and simulated results are useful for gaining insight into complex boiling flows in tubes, and provide a sound basis for further work in this area.
Keywords: CFD; Flow regimes; two-phase flow boiling; vapour quality

Two-phase flow boiling pressure drop in small channels - Sardeshpande, Madhavi V.; Shastri, Parikshit; Ranade, Vivek V. (International Journal of Heat and Fluid Flow, 2016)
Two-phase flow boiling in small channels finds a variety of applications in power and process industries. Heat transfer, boiling flow regimes, flow instabilities, pressure drop and dry out are some of the key issues related to two-phase flow boiling in channels. In this work, the focus is on pressure drop in two-phase flow boiling in tubes of 19 mm diameter. These tubes are typically used in steam generators. Relatively limited experimental database is available on 19 mm ID tube. Therefore, in the present work, the experimental set-up is designed for studying flow boiling in 19 mm ID tube in such a way that any of the different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) can be investigated by varying inlet conditions. The reported results cover a reasonable range of heat and mass flux conditions such as 9-27 kW/m(2) and 2.9-5.9 kg/m(2) s respectively. In this paper, various existing correlations are assessed against experimental data for the pressure drop in a single, vertical channel during flow boiling of water at near-atmospheric pressure. A special feature of these experiments is that time-dependent pressures are measured at four locations along the channel. The steady-state pressure drop is estimated and the identification of boiling flow regimes is done with transient characteristics using time series analysis. Experimental data and corresponding results are compared with the reported correlations. The results will be useful for understanding key aspects of flow boiling in small channels. (C) 2016 Elsevier Inc. All rights reserved.

Deployment of underground coal gasification in India - Singan, Akshay; Ranade, Vivek V. (Current Science, 2017)

Electrical resistance tomography for gas holdup in a gas-liquid stirred tank reactor - Sardeshpande, Madhavi V.; Gupta, Suraj; Ranade, Vivek V. (Chemical Engineering Science, 2017)
Gas-Liquid flows in stirred tank reactors (STR) are used in many significant industrial operations such as hydrogenation, absorption, stripping, oxidation, hydrogenation, ozonation, chlorination, fermentation, etc. Gas-Liquid STRs are expected to perform several functions such as mixing, dispersing gas into liquid, mass and heat transfer and reactions. Gas hold up distribution and various flow regimes are the key parameters affecting performance of gas-liquid STRs. Various techniques such as visual analysis, photography, light attenuation, optical probe method are used to understand gas hold-up distribution within stirred tanks. Most of these techniques have some limitations with respect to measurement of gas hold up distribution. Electrical Resistance Tomography (ERT) is an upcoming technique for obtaining both qualitative and quantitative data on multiphase process units non-invasively and non-intrusively. In this work, an attempt was made to establish and validate the ERT technique for characterizing gas-liquid flows in a laboratory scale STR using the Rushton turbine impeller. ERT was used to study gas holdup and to identify flow regimes. The results were compared with the visual measurements as well as previously published correlations. The effect of gas flow rate, impeller speed on the mean gas holdup is discussed. The methodology and results presented in this work will be useful to effectively apply ERT for characterizing gas-liquid flows in stirred tanks. (C) 2017 Elsevier Ltd. All rights reserved.

Modeling G-L-L-S reactor: a case of hydrogenation of nitrobenzene - Sharma, Deepankar V.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2017)
Gas-liquid liquid solid (GLLS) reaction systems are often encountered in manufacturing of fine and specialty chemicals. More often than not, such reaction systems involve multiple reactions, and selectivity toward the desired component always poses challenges. An adequate understanding of various parameters affecting GLLS reactor performance is essential to develop strategies for realizing desired selectivity. In this work, a comprehensive reaction engineering model for simulating four phase hydrogenation reactions has been developed. A generalized mixing cell based framework for a reaction system with four interacting phases (gas [G], aqueous [L], organic [L], and solid catalyst [S]) was developed. The model is written in a general way so as to specify one of the liquid phases as a continuous phase, and the other three phases are dispersed into it. In each cell, vapor space is included. The model includes the possibility of evaporation of solvent and internal condensation (in vapor space). The model can also be applied for a dead end (from a perspective of reacting gas) reactor. Model equations were solved using MATLAB. The equations and solution methodology were verified by comparing numerical solutions with available solutions of various limiting cases. A case of four phase hydrogenation of nitrobenzene to para amino phenol and aniline was considered to illustrate the application of the developed model. Key findings from the model were validated by comparing with laboratory scale experimental data. The model was then used to develop insights and guidelines for enhancing selectivity toward desired product. The developed model and presented results will be useful to develop general guidelines for design and optimization of GLLS reactors.

Reaction engineering of urea alcoholysis: alkyl carbamates - Mote, Dhananjay R.; Ranade, Vivek V. (Indian Journal of Chemical Technology, 2017)
Urea alcoholysis is a reversible reaction generating alkyl carbamate and ammonia as products. The reaction can be performed non-catalytically or in presence of catalyst. The first step in Reaction engineering analysis is to finalize the reactor configuration. In this case it is important to determine the necessity of reactive separation (simultaneous reaction and separation). This has been addressed by first establishing the reversibility of the reaction through theoretical and experimental investigation. Based on this analysis, an experimental setup comprising tubular reactor and a separator has been built. Experiments have been performed for different alcohols at different flow rates and temperatures. The experimental data is used to establish kinetic parameters. Systematic reaction engineering analysis based on multi-stage ideal reactors with and without simultaneous mass transfer is then carried out in terms of three dimensionless numbers. The analysis presented in this work can be readily applied to a general class of reversible reactions with volatile products and the methodology can be used to develop and design reactors for them. The approach and results presented here will be useful to establish optimal reactor configuration and design for urea alcoholysis reactions.

Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater

CFD modelling of almond drying in a tray dryer - Chilka, Amarvir G.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
Drying is important in many food processing applications, and particularly so in the dry fruits industry. This work is focused on developing computational models for simulating the drying of almonds in a tray dryer. It is important to quantitatively understand heat and mass transfer within and around a single almond particle as well as the particle-particle interactions and their implications for dryer design. In this work, we have developed a systematic CFD modelling framework for modelling almond drying in a tray dryer. A single tray filled with almonds (similar to 2 kg) were dried at three set temperatures viz., 55, 65, and 75 degrees C. Air relative humidity at the inlet and outlet locations, and the weight of almonds were measured during drying for each experiment. An additional set of experiments were conducted in which almonds were filled only in the half section of the tray, keeping the other half empty. The same amount of almonds were used, to have multiple layers of almonds in the tray, and the set temperature for the experiment was 75 degrees C. Flow, heat, and mass transfer in the tray dryer were simulated using commercial CFD software Ansys Fluent. The validated computational model was used to simulate various cases including larger and more trays. The developed approach and models will be useful to select the appropriate dryer configuration and optimize its design. The developed models will also be useful to identify suitable operation conditions for the drying of almonds as well as other food products.
Keywords: Almonds; CFD; Drying; scale-up; tray dryer

Flow, mixing, and heat transfer in fluidic oscillators - Khalde, Chirag M.; Pandit, Ajinkya V.; Sangwai, Jitendra S.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
There is an increasing emphasis on process intensification and development of compact, intensified reactors and separators in recent years. Significant efforts are being made to develop such intensified reactors and separators without any moving parts. Some of the recent research studies have proven that a liquid-liquid extractor based on the Coanda effect and feedback oscillations exhibit excellent mixing and liquid-liquid contacting. These fluidic oscillators can potentially be used for a variety of other multiphase reactions and systems demanding enhanced mixing and heat and mass transfer. In this work, we have computationally investigated flow, mixing, and heat transfer in fluidic oscillators based on the Coanda effect. Available information on flow and mixing in fluidic oscillators was critically reviewed and key gaps in the available knowledge with respect to the design and optimization of fluidic oscillators were identified. Computational flow models were developed to characterize key flow features like unsteady flows, secondary vortices, and internal recirculation over a range of Reynolds number (Re = 90-1538) for three different oscillator designs. Systematic numerical studies were carried out to quantify different flow regimes, oscillations, and the influence of key geometric parameters on flow, mixing, and heat transfer. Simulated results were critically analyzed and are presented in the form of dimensionless numbers. The approach and results presented in this work will provide useful insights and a systematic basis for extending the applications of the Coanda-based feedback oscillatory devices for a wide range of engineering applications.
Keywords: CFD; Coanda effect; fluidic oscillators; heat transfer; mixing

Hydrodynamic cavitation using vortex diode: an efficient approach for elimination of pathogenic bacteria from water - Jain, Pooja; Bhandari, Vinay M.; Balapure, Kshama; Jena, Jyotsnarani; Ranade, Vivek V.; Killedar, Deepak J. (Journal of Environmental Management, 2019)
The present study successfully demonstrates greener methodology of hydrodynamic cavitation using rotational flows for disinfection of water. Disinfection of two model microbial strains-gram-negative (Escherichia colt) and gram-positive (Staphylococcus aureus) using vortex diode was evaluated. The removal efficacy was quantified for two different cavitation reactors. Practically complete elimination of E. coli was achieved (99%) after 1 h of cavitation at a pressure drop of only 0.5 bar. However, elimination of S. aureus using vortex diode was observed to be lower in comparison to the removal of E. coli and only 60% disinfection could be achieved under similar conditions, which can be subsequently enhanced up to 98% by increasing pressure drop. The results were compared with another cavitating device that employs linear flow for cavitation, orifice. The reactor geometry has significant impact on the disinfection process and orifice was found to require significantly higher pressure drop (10 bar) conditions for disinfection and for eliminating grain-positive bacteria with high efficiency. A plausible mechanism for disinfection was proposed to elucidate the role of cavitation in cell destruction leading to death of cells through the rupture of cell wall, oxidative damage and possible DNA denaturation. Also, a cavitation model using per pass disinfection was developed that can provide meaningful physical description of the disinfection process as against the conventional first order reaction rate model. This study would provide meaningful insight into cavitation process based on hydrodynamic cavitation for the destruction of both gram-negative and gram-positive bacteria from various water sources, including industrial wastewaters.
Keywords: Cavitation; Disinfection; kinetics; pollution; Wastewater treatment

Population balance-enabled model for batch and continuous crystallization processes - Pandit, Ajinkya; Bhambure, Rahul; Ranade, Vivek V. (Chemical Engineering in the Pharmaceutical Industry, 2019)
Crystallization is a critical unit operation in manufacturing of various active pharmaceutical ingredients and drugs. Irrespective of the large-scale use of crystallization in pharmaceutical manufacturing industry, crystallization is still considered as an art. Recently, quality by design (QbD) is gaining industry acceptance as an approach toward development and commercialization of the pharmaceutical drug molecules. In QbD, the unit operations and the process are designed and controlled to deliver specified quality attributes consistently. The proposed chapter is motivated by the necessity of the prediction of crystallization events like onset of the crystallization, nucleation, and growth during crystallization of active pharmaceutical ingredients. The chapter demonstrates the integrated use of population balance modeling framework for developing a fundamental understanding of the kinetic aspects of crystallization and correlating the developed understanding for scale-up and design for the crystallization processes. Efforts are made to discuss the impact of various critical process parameters like metastable zone width, scale effects, and residence time on crystal size during batch and continuous modes with the help of couple of case studies. The presented model and approach will be useful for implementing QbD for crystallizers.

Destroying antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study reports, for the first time, a new and techno-economic strategy for effective removal of antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract. A hybrid methodology using natural oils of known health benefits has been discussed in combination with conventional physico-chemical method of hydrodynamic cavitation that not only provides efficient and effective water disinfection, but also eliminates harmful effects of conventional methods such as formation of disinfection by-products apart from reducing cost of treatment. A proof-of concept is demonstrated by achieving exceptionally high rates for practically complete removal of antimicrobial resistant (AMR) and relatively less researched, gram-negative opportunistic pathogen, Pseudomonas aeruginosa and gram-positive methicillin resistant, Staphylococcus aureus using a natural oil-Peppermint oil and two different cavitating reactors employing vortex flow (vortex diode) and linear flow (orifice) for hydrodynamic cavitation. > 99% disinfection could be obtained, typically in less than 10 min, using vortex diode with operating pressure drop of 1 bar and low dose of 0.1% peppermint oil as an additive, depicting very high rates of disinfection. The rate of disinfection can be further increased by using simple aeration which can result in significant lowering of oil dose. The conventional device, orifice requires relatively higher pressure drop of 2 bar and comparatively more time (similar to 20 min) for disinfection. The cost of the disinfection was also found to be significantly lower compared to most conventional processes indicating techno-economic feasibility in employing the developed hybrid method of disinfection for effectively eliminating bacteria including AMR bacteria from water. The developed approach not only highlights importance of going back to nature for not just conventional water disinfection, but also for eliminating hazardous AMR bacteria and may also find utility in many other applications for the removal of antimicrobial bacteria.
Keywords: AMR bacteria; Cavitation; Disinfection; Oil; Water treatment

Novel hybrid cavitation process for enhancing and altering rate of disinfection by use of natural oils derived from plants - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study is an attempt to improvise the hydrodynamic cavitation methodology for effective disinfection of water and also to suggest prototype development for practical application. The enhancement in the disinfection efficiency was evaluated specifically for the effect of pressure, temperature, pH, microbial inoculum size and also on effect of different additives for the two model microbial strains, gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus). The efficacy of the hydrodynamic cavitation is evaluated for the two types of flows/cavitation devices - linear flow in the case of orifice and vortex flow for vortex diode. The vortex diode requires significantly lower pressures, 50% lower as compared to orifice for the similar extent of disinfection. While the bacterial disinfection at high temperature is known, the usefulness of hydrodynamic cavitation is especially evident at ambient conditions and the process is effective even at very high concentrations of bacteria, not reported so far. The reactor geometry also has significant effect on the disinfection. The present study, for the first time, reports possible use of different natural oils such as castor oil, cinnamon oil, eucalyptus oil and clove oil in conjunction with hydrodynamic cavitation. The nature of oil modifies the cavitation behavior and an order of magnitude enhancement in the cavitation rate was observed for the two oils, eucalyptus and clove oil for a very small concentration of 0.1%. The increased rates of disinfection, of the order of 2-4 folds, using oil can drastically reduce the time of operation and consequently reduce cost of disinfection. A possible mechanism is proposed for the effect of oil and hydrodynamic cavitation in cell destruction through the rupture of cell wall, oxidative damage and possible DNA denaturation. A cavitation model using per pass disinfection was used to correlate the data. The increased efficiency using oils and possible benefits of the developed process, where natural oils can be perceived as biocatalysts, can have significant advantages in practical applications.
Keywords: Antimicrobial; Cavitation; Disinfection; Oil; Wastewater treatment

Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Safe water and technology initiative for water disinfection: application of natural plant derived materials - Mane, Maya B.; Bhandari, Vinay M.; Ranade, Vivek V. (Journal of Water Process Engineering, 2021)
Safe drinking water is the necessity of life. The present study reveals use of natural resources such as plant extracts and natural oils for water disinfection. Differences between oil and water soluble additives were highlighted for plant extracts and insoluble natural oils. A hybrid hydrodynamic cavitation process was quite effective in both the cases and high rates of disinfection were achieved. Studies were reported using oils (ginger, turmeric, lavender, tulsi) and rhizome derived plant extracts such as ginger, turmeric and mango ginger, as additives in process intensification (0.1% v/V). A vortex based cavitation device (vortex diode, nominal capacity 1 m3/h) was used with pressure drop of 1 bar. A high disinfection of 96% and 88% was obtained in 15 min for ginger oil and mango ginger extract respectively as compared to 44% using cavitation alone. Acoustic cavitation gave 94% and 30% disinfection with and without additive-mango ginger extract. The FTIR analyses before and after cavitation, with ginger additive, showed no by-products formation and indicated gingerol as active component in disinfection. The per-pass disinfection values were also higher, up to 5 times than cavitation alone. Hybrid hydrodynamic cavitation using natural plant derived materials can offer a promising technology alternative in water disinfection.
Keywords: Cavitation; Disinfection; Natural oil; Plant extract; Water treatment

Wastewater treatment and process intensification for degradation of solvents using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Chemical Engineering and Processing-Process Intensification, 2021)
Industrial wastewater treatment for removal of small concentrations of harmful solvents is pertinent issue in many chemical and pharmaceutical industries. The present work evaluates removal of three common solvents by hydrodynamic cavitation (nominal capacity, 1m(3)/h). Solvent degradation of three solvents viz. octanol, dimethyl formamide and cyclohexanol was studied in the concentration range of 50-200 mg/L and for the pressure drop range of 0.5-5 bar. The vortex based cavitation device (vortex diode) was compared with that of linear flow based device (orifice). Process intensification in the form of aeration and addition oxidizing agent-hydrogen peroxide was also evaluated for synergistic effect. The vortex diode required lower pressure drop and is superior to orifice and process intensification using aeration is most effective. A reduction in TOC to the extent of 74% could be achieved for octanol (200 ppm) using aeration with cavitational yield of 1202x10(-4) mg/J for vortex diode, yield similar to 10 times of orifice. The degradation depends on the nature of solvent and it was revealed that low values of dielectric constant (epsilon<10) favour degradation. The kinetics was evaluated using rate model based on per-pass degradation factor. The process techno-economic feasibility is useful in industrial wastewater treatment.
Keywords: Cavitation; Effluent; Organics removal; Oxidation; pollution

Hydrogen solubility in biphasic liquid reaction mixture of cinnamaldehyde hydrogenation: experimental and mathematical modeling study - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Journal of Chemical Sciences, 2022)
The solubility of hydrogen in the biphasic reaction mixture of cinnamaldehyde hydrogenation at 298 to 353 K has been determined in this work experimentally and by using a thermodynamic model. It is evident from many studies that the addition of extra phase, aqueous KOH as the fourth phase, to the three-phase cinnamaldehyde hydrogenation mixture [gas (hydrogen)-liquid (cinnamaldehyde + toluene)-solid (catalyst)] leads to enhancement of cinnamyl alcohol selectivity to a great extent. Determination of hydrogen solubility in this biphasic (organic-aqueous) reaction mixture is crucial to understand the intrinsic reaction kinetics of this reaction. The solubility of hydrogen was experimentally determined using a pressure drop method and reported in terms of Henry's constant. Firstly, hydrogen solubility was determined in pure components viz. toluene, cinnamaldehyde, and water followed by determination of its solubility in the cinnamaldehyde-toluene mixture, aqueous KOH, and eventually, in the reaction mixture containing the two immiscible liquid phases. The effect of changing concentrations in these mixtures and changing phase holdups in the total reaction mixture on hydrogen solubility was studied. Starting from pure components to the reaction mixture, the hydrogen solubility was predicted using a two-step thermodynamic approach involving regular solution theory and the theory of corresponding states. The solubility predictions from this thermodynamic model will be helpful in the accurate estimation of kinetic parameters.
Keywords: biphasic liquid mixture; gas-liquid-liquid-solid [GLLS]; hydrogen solubility; Hydrogenation; thermodynamic model

Continuous hydrogenation of cinnamaldehyde: gas-liquid-liquid-solid helical coil reactor - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2023)
The advantages and challenges of using the gas-liquid-liquid-solid(GLLS) hydrogenation system are discussed in this work using the caseof selective hydrogenation of cinnamaldehyde to cinnamyl alcohol (animportant ingredient in the perfume and flavoring industry). The fourphases in this system include gas (hydrogen)-liquid (organic, reactant+ solvent)-liquid (aqueous KOH)-solid (5% Pt/C catalyst). The additionof second liquid phase, i.e., aqueous KOH significantly increasesselectivity toward cinnamyl alcohol compared to the conventional three-phasehydrogenation. The four-phase GLLS reactions were carried out andoptimized in a continuous helical coil reactor. The role of key aspectssuch as gas solubility, kinetics, flow hydrodynamics, axial dispersion,and mass transfer on the performance of a continuous GLLS reactoris presented and discussed in this work. The presented results anddiscussion will be useful for addressing conflicting demands likelong residence time, low axial dispersion, and high mass transfer.The experimental studies and results of the developed mathematicalmodel indicate that the continuous GLLS helical coil reactor outperformsthe batch operation. The production rates (kg day(-1)) of cinnamyl alcohol achieved in continuous operation were at leastdouble in comparison to batch operation, with 32% less consumptionof precious catalyst (per kg of product). The presented results will open up new opportunities for enhancing selectivity and overall performanceof hydrogenations via introducing a second immiscible liquid phaseand designing continuous tubular reactors for the same.